LOGISTICS RISK RESEARCH OF PREFABRICATED HOUSE CONSTRUCTION ENGINEERING BASED ON CREDIBILITY METHOD - Xiaoping Bai; Huifang Zhao (Civil Engineering Journal, 2017)
In recent years, the prefabricated house industry has rapid development,.Because of fewer suppliers, higher demand transport scheme and complex quality test, the risks of construction engineering logistics links are relatively high. Studying how to effectively evaluate the risks of construction engineering logistics links is significant. According to the characteristics of the prefabricated house construction engineering, we analyse the construction engineering logistics risks and use the combined weights method to determine the weight of indexes which contains both subjective and objective factors, to improve the scientific value and the validity of the assessment. Based on credibility measure method, a new logistics risk evaluation model in prefabricated housing is established to estimate the risk during making prefabricated house construction engineering. The presented model can avoid the subjectivity of selecting the membership function and solve the problem of how to comprehensively assess the construction engineering logistics risk in a certain extent.